Anti-Diabetic and Antioxidant Effects of Methanolic Flower Head Extract of Tagetes Patula in Streptozotocin and Dexamethasone Induced Diabetic Rats: Pharmaceutical Science-Pharmacology for drug discovery - M. Ganga Raju; Gayathri S; N V L Suvarchala Reddy V; Anusha K; Pavani K (International Journal of Life Science and Pharma Research, 2022)
Diabetes is a chronic metabolic disorder characterized by a high blood glucose concentration, i.e., hyperglycemia or caused by insulin deficiency, often combined with insulin resistance. In the Present study, the antidiabetic and antioxidant activity of the methanolic extract of Tagetes patula flower heads was screened out in rodent models. The pharmacological evaluation was carried out using 200 and 400 mg/kg, b.w. The in-vivo antidiabetic activity was performed in streptozotocin, dexamethasone- induced diabetic models and oral glucose tolerance test. Metformin hydrochloride was used as a standard. The parameters like blood glucose levels, insulin levels, homeostasis assessment of insulin resistance, insulin sensitivity, and fasting glucose-insulin ratio were estimated in these models. The in-vitro antioxidant activity of methanolic extract of Tagetes patula was performed by using hydroxyl radical scavenging assay and Ascorbic acid was used as a standard. The preliminary phytochemical screening of Tagetes patula revealed the presence of phytoconstituents like alkaloids, flavonoids, saponins, steroids, phenols, carbohydrates, triterpenoids, and tannins. The extract showed a significant decrease in the elevated blood glucose levels in streptozotocin, dexamethasone-induced diabetic models, and also in the oral glucose tolerance test. The extract prevented insulin resistance and significantly increased insulin sensitivity in the dexamethasone-induced model. The various phytochemical constituents like alkaloids, flavonoids, saponins, steroids, and phenols might be responsible for lowering the blood glucose levels in the animal models mentioned above. The extract showed significant scavenging activity against hydroxyl free radicals. From the above outcomes, it is flawless that the methanolic extract of Tagetes patula has antidiabetic and antioxidant activities.